2015
DOI: 10.12973/eurasia.2015.1306a
|View full text |Cite
|
Sign up to set email alerts
|

In-service Teachers’ Implementation and Understanding of STEM Project Based Learning

Abstract: In this study, we discussed the participating teachers" implementation and understanding of science, technology, engineering and mathematics (STEM) project based learning (PBL). A research team at a STEM center systematically offered professional development activities to 92 teachers in an urban school district in the southern U.S. To investigate the teachers" implementation and understanding of the STEM PBL pedagogy, we conducted a collective case study with five teachers. Study data included interviews, in-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
111
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(127 citation statements)
references
References 24 publications
9
111
0
7
Order By: Relevance
“…While the number of STEM education initiatives across countries is rapidly increasing, not much is known about approaches for the implementation of integrated STEM instruction [5,27,28]. Teachers' understanding and application of STEM activities were explored using a qualitative case study approach [29]. The results suggest that in applying STEM in the classroom, the teacher should: (1) pay attention to the academic level of the students; (2) prepare as best as possible; and (3) try hard to apply STEM learning.…”
Section: The Domain Of Attitude Knowledge and Application Of Stemmentioning
confidence: 99%
“…While the number of STEM education initiatives across countries is rapidly increasing, not much is known about approaches for the implementation of integrated STEM instruction [5,27,28]. Teachers' understanding and application of STEM activities were explored using a qualitative case study approach [29]. The results suggest that in applying STEM in the classroom, the teacher should: (1) pay attention to the academic level of the students; (2) prepare as best as possible; and (3) try hard to apply STEM learning.…”
Section: The Domain Of Attitude Knowledge and Application Of Stemmentioning
confidence: 99%
“…Findings from several engineering-design-based studies showed increased student content knowledge (Mehalik, Doppelt, & Schuun, 2008;Richards, Hallock, & Schnittka, 2007;Schnittka, 2009). Furthermore, science content knowledge was more often influenced by engineering-design-based practices than by inquiry practices (e.g., Nite, Capraro, Capraro, Morgan, & Peterson, 2014;Han, Capraro, & Capraro, 2014;Han, Yalvac, Capraro, & Capraro, 2015). Engineering design was often associated with greater affect and academic interest for formerly low achieving African American students than for any other group of students.…”
Section: Themes From Higher Level Abstractionsmentioning
confidence: 99%
“…The reason is that beyond making the comprehensive overlook and survey on the relative researches in the online education relative research fields (Anderson & McGreal, 2012;Casey, 2012;DeWaard et al, 2011;Han, Yalvac, Capraro, & Capraro, 2015;Hyman, 2012), the majority of the related researches always emphasize the traditional physical course's requests, such as the course's professionalization, evaluation and certification (Chamberlin & Parish, 2011;Eilks, 2015) without discussion and analyzing the correlationships between HESSI, CEOTPD and HEOSDS. Therefore, in order to significantly resupply these research gaps that no research can comprehensively analyze and further explore the most decisive online education determinants of sustainable strategy for Taiwanese higher education in the New Southbound Policy through interplay analysis between higher education students' studying interests and corporate employees' on-the-job digital training desires in the contemporary electronic-cloud era in consideration of empirical conditions among HE student digital effections, corporate digital on-the-job digital training demands and HE institute sustainable development for the New Southbound Policy requirements.…”
Section: Colleges Universities Totalmentioning
confidence: 99%